Bismuth-Remaining Cupellation Fire Assay Preconcentration Combined with Inductively Coupled Plasma Mass Spectrometry for the Simultaneous Determination of Ultratrace Au, Pt, Pd, Ru, Rh, and Ir in Geologic Samples - Wenshan Ni; Xiangju Mao; Mingxing Yao; Qiliang Sun; Xiaorui Guo; Hongli Zhang; Lu Liu (International Journal of Analytical Chemistry)
In this work, a novel method of bismuth fire assay (Bi-FA) combined with inductively coupled plasma mass spectrometry (ICP-MS) simultaneous determination of ultratrace gold (Au), platinum (Pt), palladium (Pd), ruthenium (Ru), rhodium (Rh), and iridium (Ir) in geologic samples was established. Bismuth oxide (Bi2O3) was used as noble metal elements fire assay collector, and Bi-remaining protection cupellation was employed to generate Bi granule. After the Bi granule was microwave-digested by aqua regia (40%, v/v), 197Au, 195Pt, 106Pd, 101Ru, 103Rh, and 193Ir in the sample solution were determined by ICP-MS. Using Bi as cupellation protector, volatile Ru could be collected effectively and without volatilization loss during microwave digestion and decompression. Moreover, the toxicity of Bi was exceptionally low compared to toxic nickel oxide and lead oxide in nickel sulfide/lead fire assay; thus Bi-FA was a green environmental analysis method. The mineral composition and decomposition character of chromite, black shale, and polymetallic ore were investigated, and pretreatment procedures were optimized for such special samples. Besides, the influence of mass spectrum interference of coexisting elements was discussed. Under the optimal conditions, excellent curve fittings of Au, Pt, Pd, Ru, Rh, and Ir were obtained between 0.01 and 100 ng·mL−1, with the correlation coefficients exceeding 0.9995. The detection limits were from 0.002 ng·g−1 to 0.025 ng·g−1. The developed method was applied to analyze the Chinese Certified Reference Materials (CRMs) and the determined values were in good agreement with the certified values.